Dual aggregation in ground state and ground-excited state induced by high concentrations contributes to chlorophyll stability. (30th July 2022) - Li, Fangwei; Cao, Jiarui; Wang, Zhenhao; Liao, Xiaojun; Hu, Xiaosong; Zhang, Yan
Highlights: The high-concentration treatment improves chlorophyll stability was first posed. A stable structure model of Chl a "sandwich" dimer was first described. The interaction in the Chl dimer was first described. Quantum chemical calculations and experiment were combined to explain the mechanism. Abstract: Chlorophyll (Chl) has great application potential in food colouring and nutritional supplementation. Since Chl is easily degraded, stability protection is vital to its application. Herein, a dual aggregation mechanism induced by high concentrations to improve Chl stability was proposed. As a result, the Chl retention at high concentrations increased to 323.92% of that at low concentrations. To explain aggregation, the Chl dimer was observed by atomic force microscopy, and a stable structural model of the Chl a "sandwich" dimer was established. It was proven that Chl dimer stability was dominated by van der Waals (vdW) interactions, while monomer orientation during aggregation was dominated by electrostatic interactions. Charge transfer (CT) was also shown to be a key interaction in the dimer. Excitation at 393 nm was first proposed for CT identification. This research hopes to provide new ideas for the design of food ingredients in human health promotion.